Political and historical discourse in the making relationship between the Czech Republic and European Union in 1993-1998 - Anton Liahusha (Cхід, 2013)
The paper described the factors shaped the content and structure of relationships between the Czech Republic and the European Union. The author has analyzed the political and historical discourses that have been changed in the EU and in the Czech Republic as well, and this process created a historical reality through the 1993-1998 period. It was used methods of discourse analysis and comparative studies, due to this approach the author reached a conclusion that the relationships were driven by reciprocating nature and transformation processes in the supranational union and in the post-communist countries. The author describes  the way of the Czech Republic's foreign policy that correlates with its European integration policy. The article describes the institutional and political changes that took place in the European Union in the context of its enlargement to the East.